2018
DOI: 10.1002/uog.18926
|View full text |Cite
|
Sign up to set email alerts
|

Does site of cord insertion increase risk of adverse outcome, twin‐to‐twin transfusion syndrome and discordant growth in monochorionic twin pregnancy?

Abstract: Velamentous cord insertion in one or both twins increases the risk of adverse outcome and TTTS, irrespective of discordance in the insertion sites, whereas the risk of discordant growth is determined by both discordance in insertion sites and velamentous cord insertion in one twin. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 33 publications
2
36
1
1
Order By: Relevance
“…Monitoring of Type‐III sFGR is particularly challenging since IUD is unpredictable and the risk of neurological injury to the larger twin is substantial. Known adverse predictors in sFGR include earlier gestational age at diagnosis, ductus venosus Z ‐score, cord insertion site and fetal weight discrepancy, but further development of prognostic markers for severe sFGR is needed. In general, severe sFGR with normal venous Doppler can be managed expectantly with frequent Doppler, biophysical profile and cardiotocographic evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring of Type‐III sFGR is particularly challenging since IUD is unpredictable and the risk of neurological injury to the larger twin is substantial. Known adverse predictors in sFGR include earlier gestational age at diagnosis, ductus venosus Z ‐score, cord insertion site and fetal weight discrepancy, but further development of prognostic markers for severe sFGR is needed. In general, severe sFGR with normal venous Doppler can be managed expectantly with frequent Doppler, biophysical profile and cardiotocographic evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that VCI may be detected at 16 weeks' gestation and at 11‐14 weeks' gestation by gray scale and color Doppler . Previous reports analyzed the risk of TTTS with the data of CI at 16 weeks' gestation . Their PPV and NPV values for prediction of TTTS by VCI (22% and 90%) compared favorably with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports analyzed the risk of TTTS with the data of CI at 16 weeks' gestation . Their PPV and NPV values for prediction of TTTS by VCI (22% and 90%) compared favorably with our results. Improved screening techniques in the first trimester may identify high‐risk MCDA twins who require more stringent follow‐up and management, resulting in an improved prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations